On the improvement of the single-site lightning distance estimation by using the time-delay correction - Zhou, Jiahao; Zhang, Qilin; Song, Lin; Zhang, Junchao; Dai, Bingzhe; Li, Jie; Yang, Jing; Wang, Yao; Gu, Jiaying; Zeng, Jinquan (Frontiers in Earth Science, 2023)
Due to the propagation effect, the arrival time of the ground wave peak is delayed when sferics propagate at long distances. In this work, we propose a new method combined with a numerical algorithm to correct the effect of the ground wave peak time delay and calculate the ionosphere height using the difference between the arrival time of the ground wave and the skywave. The results showed that, with each increase of the propagation distance by 100 km, the delay in arrival time of the ground wave peak increased by an average of 0.9 μs. For the first and second reflectance heights, the maximum heights observed at night were 86 km and 89 km, and the minimum heights during the day were 66 km and 69 km, respectively. Using the difference in arrival time between the ground wave and skywave and the ionosphere equivalent reflection height, a single site was used to estimate the distance of lightning occurring within 900 km. This method had an average relative error of 14.6%, an average absolute error of 128.8 km, and a median distance error of 52.6 km. Finally, the percentage of data with an estimated deviation within 10% increased from 52% to 65%.